2017
DOI: 10.1016/j.amjmed.2017.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Physical Activity and Body Mass Index on Mortality in Coronary Heart Disease: Data from the Nord-Trøndelag Health Study

Abstract: Overweight and obese subjects with coronary heart disease had reduced all-cause and cardiovascular disease mortality, but such an obesity paradox was seen only in participants who did not adhere to current recommendations of physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 44 publications
5
31
1
2
Order By: Relevance
“…Using data from the Nord‐Trøndelag Health Study (HUNT), a large population‐based prospective study, Moholdt et al . found that all‐cause mortality risk was essentially equal across BMI categories in patients with a high physical activity level and sustained physical activity seemed to be more important than weight loss that associated with improved survival in CAD for long‐term prognosis .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Using data from the Nord‐Trøndelag Health Study (HUNT), a large population‐based prospective study, Moholdt et al . found that all‐cause mortality risk was essentially equal across BMI categories in patients with a high physical activity level and sustained physical activity seemed to be more important than weight loss that associated with improved survival in CAD for long‐term prognosis .…”
Section: Discussionmentioning
confidence: 91%
“…Physical inactivity and low cardiorespiratory fitness have long been recognized as major risk factors of cardiovascular disease . Physical activity is a major determinant of cardiorespiratory fitness, despite cardiorespiratory fitness is partly genetically determined . Substantial evidence has suggested that physical activity or cardiorespiratory fitness alters the association between obesity and prognosis in patients with CAD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 33 studies in over 100, 000 individuals observed that every 1 estimated MET increase in CRF was associated with 13 and 15% reductions in all-cause and CVD mortality (Nauman et al 2017). Cardiorespiratory fitness is important even in the presence of other risk factors and shown to be protective even in men with metabolic syndrome (Katzmarzyk et al 2004) and obesity (Moholdt et al 2017).…”
Section: Physical Activitymentioning
confidence: 99%
“…Although suggestions for future definitions and measurement tools for obesity are outside the scope of this critique, it would have been helpful if the Report acknowledged the current debates on the meaning and value of BMI [ 22 ], acknowledged the debates on the relationship between BMI and mortality risk [ 25 – 27 ], discussed the limitations of BMI, and highlighted the need for more research in the diagnosis and measurement of obesity. Furthermore, it would have been appreciated if the Report highlighted the importance of measuring people's bodies sensitively by ensuring respect towards patients and preserving their dignity when weighing or measuring their bodies.…”
Section: The Senate Report On Obesity: a Critiquementioning
confidence: 99%